2014
DOI: 10.1155/2014/384565
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Seed Size ofAfzelia quanzensison Germination and Seedling Growth

Abstract: Afzelia quanzensis Welw is a valuable timber producing tree species in Africa. A study was conducted to evaluate the influence of seed size on seed germination and seedlings quality of Afzelia quanzensis. Seed was categorized into three groups in regard to their length, small (<1.5 cm), medium (≥ 1.5 ≤ 2.5 cm), and large (>2.5 cm). The treatments were completely randomized into four replications. Germination percentage was not significantly ( > 0.05) different between the treatments, although large seeds had t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
1
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 12 publications
0
25
1
4
Order By: Relevance
“…As mentioned before, germination efficiency is largely affected by seed mass [27][28][29][30][31][32][33][34]. Heavier seeds are more likely to germinate and produce seedlings because plump seeds are more abundant in storage compounds that are essential for germination.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As mentioned before, germination efficiency is largely affected by seed mass [27][28][29][30][31][32][33][34]. Heavier seeds are more likely to germinate and produce seedlings because plump seeds are more abundant in storage compounds that are essential for germination.…”
Section: Discussionmentioning
confidence: 99%
“…Seed viability, germinative energy, and germination capacity are the main determinants of seed quality [27]. According to many authors, germination efficiency is largely correlated with seed mass, but plumper seeds do not always germinate faster than small seeds [27][28][29][30][31][32][33][34]. In tree nurseries, seeds are sorted into different size fractions to promote even germination.…”
Section: Introductionmentioning
confidence: 99%
“…Such variations in seed weight between the cultivars (Sadeghi, 2011), genotypes (Ashirvar, 2012) and species (Li et al, 2015) have been recorded in other plants. The seeds of both the crosses also varied significantly in length and width between three size classes as reported in Afzelia quenzensis (Mtambalika et al, 2014). It is reported that, seed-size is a plastic trait of the plants (Souza and Fagundes, 2014) and the individual seed-size (mass) in a species varies from nearly constant (Fenner, 1995) to as high as 16-fold (Hawk and Maun, 1989) and several factors may be responsible for this type of variation (Shaukat et al, 1999).…”
Section: Seed Size Variationmentioning
confidence: 65%
“…Аналогічні результати маси насіння до наших досліджень для Р. abies та P. pungens наведені у роботі Kaliniewicz (2018). Слід зазначити, що від маси та розмірів насіння в значній мірі залежать життєздатність сходів та подальший розвиток сіянців [25]. Показники енергії проростання та лабораторної схожості насіння у Р. abies з насаджень контролю були достовірно вищими, ніж у цих рослин з насаджень парків, автомагістралей та біля промислових підприємств в середньому у 1,5; 2,0; 8,2 та 1,4; 1,9; 5,6 разів відповідно.…”
Section: рис 1 картосхема розташування досліджених насаджень Pісеа unclassified